One year later, why are people still avoiding covid-19 news?: understanding predictors of news avoidance in Indonesia - Yearry Panji Setianto; Puspita Asri Praceka (Penerbit Universiti Kebangsaan Malaysia, 2023)
The global effect of COVID-19 pandemic has continued for almost two consecutive years. Indonesia is also among the countries most impacted by the SARS-CoV2 virus under this period. Consequently, certain challenges tend to occur as regards public interest in accessing or deterring recent information associated with the disease. While there are increasing interests among media and communication scholars in understanding why people are avoiding news, little attention has been given to this audience behaviour during a global crisis like coronavirus outbreak. Using news avoidance as the main concept, this research is aimed at examining the critical factors that influence news avoidance in low-choice media environments, particularly in the Global South like Indonesia. Employing a face-to-face survey with 1,000 participants in Banten Province, Indonesia, this study found that younger people with lesser interest in COVID-19 related issues appear more prone to avoid this news, in addition to their level of news overload. Nevertheless, we also found that gender and the level of education factors did not influence whether people distanced themselves with negative coverage of coronavirus news in the country during the first year of the pandemic. Furthermore, the perception of information overload and minimal trust in news sources greatly contributed to the avoidance situation.